Traveling solitary wave solutions for the symmetric regularized long-wave equation (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we employ the extended tanh function method to nd the exact traveling wave solutions involving parameters of the symmetric regularized long- wave equation. When these parameters are taken to be special values, the solitary wave solutions are derived from the exact traveling wave solutions. These studies reveal that the symmetric regularized long-wave equation has a rich varietyof solutions.